1989
DOI: 10.1172/jci114259
|View full text |Cite
|
Sign up to set email alerts
|

In vivo handling of soluble complement fixing Ab/dsDNA immune complexes in chimpanzees.

Abstract: We used soluble, C-fixing antibody/dsDNA IC to investigate immune complex (IC) handling and erythrocyte (E)-to-phagocyte transfer in chimpanzees. IC bound efficiently to chimpanzee E in vitro and showed minimal release with further in vitro incubation in the presence of serum in EDTA (c 15% within 1 h). These IC also bound rapidly to E in vivo (70-80% binding within 1 min) and did not show detectable release from E in the peripheral circulation after infusion in vivo (< 2% within 1 h). Despite such slow C-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 51 publications
2
31
1
1
Order By: Relevance
“…Fc␥RIIIa may also play a critical role in the first-dose cytokine-release syndrome seen with some therapeutic monoclonal antibodies (57). Furthermore, our earlier studies in a primate model of immune complex handling demonstrated an essential role for Fc␥RIIIa (58,59), and more recent observations in mice with targeted disruption of murine Fc␥RIII also support an important role in immune complex-mediated triggering of inflammatory reactions (60).…”
Section: Discussionmentioning
confidence: 65%
“…Fc␥RIIIa may also play a critical role in the first-dose cytokine-release syndrome seen with some therapeutic monoclonal antibodies (57). Furthermore, our earlier studies in a primate model of immune complex handling demonstrated an essential role for Fc␥RIIIa (58,59), and more recent observations in mice with targeted disruption of murine Fc␥RIII also support an important role in immune complex-mediated triggering of inflammatory reactions (60).…”
Section: Discussionmentioning
confidence: 65%
“…The mechanism by which bona fide complement-fixing IC are cleared from the circulation after binding to CR1 on RBCs is controversial (6,9,11,26). If, as suggested, there is a proteolytic step or recognition and binding by fixed Fc receptors of the reticuloendothelial system, then safe and rapid clearance should occur.…”
Section: Methodsmentioning
confidence: 99%
“…It is unlikely the franked RBCs would be removed from the circulation. The maximum amount of mouse IgG bound to the RBCs (500-1000 IgG/ RBC) is less than is seen when IC are bound (14), and primate studies demonstrate that such RBCs containing IC are not cleared (5,6,9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with PNH have been shown to have normal levels of FcyRIIINK and FcyRIIIM,, (21)(22)(23) but are deficient in Fc~yRIIIPMN (18,19), consistent with the neutrophil isoform having a GPI anchor. Since CD 16 participates in the handling of immune complexes and certain bacteria (24)(25)(26)(27), a generalized deficiency in Fc-yRIIIPMN might lead to significant impairment of host defenses. However, the absence ofprominent immune complex-mediated disease, frequent bacterial infections, and recurrent viral infections (1, 28,29) suggests either that CD 16 is not essential for protection ofthe host or that it is not totally deficient on PNH PMN.…”
mentioning
confidence: 99%